TURİZM İŞLETMELERİNDE KALİTE MALİYETLERİ YÖNETİMİ VE OTEL İŞLETMELERİ ÜZERİNDE BİR İNCELEME - Şi̇mşek, Kezban; Karakaya, Mevlüt (Sosyal Bilimler Ensititusu Hakemli Dergisi Oneri, 2016)
Intense competition in today business world makes offer of qualified goods and services essential in tourism businesses as it is in manifacturing businesses. To continue their existence, these profit-oriented businesses have to have an active quality costs system which follows cost of exercises to provide quality, keeps them under control besides providing quality. This study reveals managers’ opinion and present state of 3,4 and 5-star hotel businesses according to their quality costs applications. In this sense, hotel managers’ aspects of quality costs and their activities within quality costs were tired to be evalu ated, as a result of the study, it was discovered that essential part of the hotel businesses (67,2 %) didn’t have quality costs system.
Keywords: Kalite; Kalite Maliyetleri; Kalite Maliyetleri Sistemi